The Genus Aspergillus Pathogenicity, Mycotoxin Production and Industrial Applications - Razzaghi-Abyaneh, Mehdi; Rai, Mahendra (IntechOpen, 2022)
This book highlights recent advances in the pathogenicity, mycotoxin-producing ability, and industrial application of members belonging to the genus Aspergillus. It is divided into two sections and six chapters that address different aspects and the importance of Aspergilli in relation to Aspergillus-human interactions, immunopathogenesis of invasive aspergillosis, the role of aflatoxin in Aspergillus flavus resilience to stress, mycovirus-containing A. flavus and carcinogenesis beyond mycotoxin production, and industrial application of Aspergillus species in conjunction to nanoparticle synthesis. This book brings readers several cutting-edge aspects of Aspergillus research with useful information for mycologists, microbiologists, toxicologists, plant pathologists, and pharmacologists, who may be interested in understanding the impact, significance, and recent advances within the genus Aspergillus that have not been critically noticed elsewhere.